Method for manufacturing adhesive sheet, method for manufacturing optical laminate, and method for manufacturing image display device
Patent Information
- Application Number
- CN202280036391.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-21
- Filing Date
- 2022-05-20
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-05-20
AI Technical Summary
In the prior art, the optical film undergoes excessive dimensional changes when the temperature changes, leading to light leakage and uneven color in the image display device. At the same time, increasing the elastic modulus of the adhesive sheet will impair its durability and transparency.
By controlling the Hansen solubility parameter Ra between (meth)acrylic polymers and isocyanate crosslinking agents to be below 15 and heating within a specific temperature and time range, an adhesive sheet is formed, suppressing dimensional changes in the optical film while ensuring durability and transparency.
It effectively suppresses dimensional changes in the optical film within the optical laminate, maintains the durability and transparency of the adhesive sheet, and is suitable for image display devices with narrow bezels.
Smart Images

Figure CN117460800B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing adhesive sheets, a method for manufacturing optical laminates, and a method for manufacturing image display devices. Background Technology
[0002] In recent years, image display devices, represented by liquid crystal displays and electroluminescent (EL) displays (e.g., organic EL displays and inorganic EL displays), have been rapidly gaining popularity. These various image display devices typically have a stacked structure of image forming layers such as a liquid crystal layer and an EL light-emitting layer, and an optical stack comprising an optical film and an adhesive sheet. The adhesive sheet is mainly used for bonding between the films contained in the optical stack and for bonding the image forming layer to the optical stack. Examples of optical films include polarizers, retardation films, and polarizers with retardation films that integrate polarizers and retardation films. An example of an optical stack is disclosed in Patent Documents 1 and 2.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2008-031214
[0006] Patent Document 2: Japanese Patent Application Publication No. 2009-98665 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] Excessive dimensional changes in optical films due to temperature variations can cause light leakage and color inhomogeneity in image display devices. These issues are particularly prevalent in larger image display devices using polarizers with retardation films. Furthermore, with the increasing prevalence of image display devices with narrower bezels (bezel-less designs), suppressing dimensional changes is becoming increasingly important. To suppress dimensional changes, increasing the elastic modulus of the adhesive sheet contained in the optical laminate can be considered. However, simply increasing the elastic modulus can sometimes lead to reduced durability of the adhesive sheet, making it unable to keep up with dimensional changes, and can also compromise the transparency desired for optical adhesive sheets.
[0009] The object of the present invention is to provide a method for manufacturing an adhesive sheet suitable for the manufacture of an adhesive sheet, wherein the adhesive sheet can suppress dimensional changes of the optical film contained in the optical laminate, and the durability and transparency are also ensured.
[0010] Problem Solving Methods
[0011] This invention provides a method for manufacturing an adhesive sheet, the method comprising:
[0012] A coating film containing an adhesive composition comprising a (meth)acrylic acid polymer (A) as a main component and further comprising an isocyanate crosslinking agent (B) is heated to form an adhesive sheet from the coating film.
[0013] When considering the self-polymer (C) of the aforementioned isocyanate crosslinking agent (B), the distance Ra of the Hansen solubility parameter (HSP) between the aforementioned (meth)acrylic acid polymer (A) and the aforementioned self-polymer (C) is 15 or less.
[0014] The heating conditions described above satisfy the following equation (1) or (2).
[0015] x≤120···(1)
[0016] x>120 and y≤-2.17x+365.83···(2)
[0017] Where x and y represent the heating temperature (°C) and heating time (seconds), respectively.
[0018] In another aspect, the present invention provides a method for manufacturing an optical laminate comprising an adhesive sheet and an optical film, the method comprising:
[0019] The adhesive sheet described above is formed using the method for manufacturing the adhesive sheet of the present invention.
[0020] In other aspects, the present invention provides a method for manufacturing an image display device, the image display device comprising an optical laminate including an adhesive sheet and an optical film, the method comprising:
[0021] The adhesive sheet described above is formed using the method for manufacturing the adhesive sheet of the present invention.
[0022] The effects of the invention
[0023] The manufacturing method of the present invention is suitable for manufacturing adhesive sheets that can suppress dimensional changes in the optical films contained in the optical laminates and ensure durability and transparency. Attached Figure Description
[0024] Figure 1 This is a schematic cross-sectional view showing an example of an adhesive sheet obtained by the manufacturing method of the present invention.
[0025] Figure 2 This is a schematic cross-sectional view showing an example of an optical laminate having an adhesive sheet obtained by the manufacturing method of the present invention.
[0026] Figure 3 This is a schematic cross-sectional view showing an example of an optical laminate having an adhesive sheet obtained by the manufacturing method of the present invention.
[0027] Figure 4 This is a schematic cross-sectional view showing an example of an optical laminate having an adhesive sheet obtained by the manufacturing method of the present invention.
[0028] Figure 5 This is a schematic cross-sectional view showing an example of an optical laminate having an adhesive sheet obtained by the manufacturing method of the present invention.
[0029] Figure 6 This is a schematic cross-sectional view illustrating an example of an image display device equipped with an adhesive sheet obtained by the manufacturing method of the present invention.
[0030] Figure 7 This is a graph showing the manufacturing conditions (main heating temperature and time) and the overall evaluation results of the adhesive sheets produced in the embodiments and comparative examples. Detailed Implementation
[0031] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The present invention is not limited to the embodiments shown below.
[0032] In this specification, "(meth)acrylic acid" refers to acrylic acid and methacrylic acid. Additionally, "(meth)acrylate" refers to acrylate and methacrylate.
[0033] [Manufacturing method of adhesive sheet]
[0034] The manufacturing method of this embodiment includes heating a coating film containing an adhesive composition (I) as a main component (meth)acrylic acid polymer (A) and further containing an isocyanate crosslinking agent (B) to form an adhesive sheet. Hereinafter, the heating of the coating film will be described as main heating. In main heating, the heat-based crosslinking and curing of the adhesive composition (I) contained in the coating film is mainly carried out. The adhesive composition (I) containing the isocyanate crosslinking agent (B) is suitable for forming an adhesive sheet with ensured durability.
[0035] When considering the self-polymer (C) of the isocyanate crosslinking agent (B), the distance Ra of the Hansen solubility parameter (HSP) between the (meth)acrylic acid polymer (A) and the self-polymer (C) is less than 15. The isocyanate crosslinking agents (B) sometimes react with each other due to the heat during the formation of the adhesive sheet, forming self-polymers of the crosslinking agent (B). The formation of these self-polymers can contribute to the formation of adhesive sheets that suppress dimensional changes in optical films by increasing the cohesiveness of the adhesive sheet. However, when the compatibility between the (meth)acrylic acid polymer (A) and the self-polymer is low, the durability and transparency of the adhesive sheet tend to decrease. This decrease can be attributed to the tendency for self-polymer-rich, independent domains to form within the adhesive sheet. The formation of these domains can cause whitening of the adhesive sheet due to light scattering and reflection at the domain interfaces, and can also cause voids (cavities) due to peeling at the domain interfaces when the adhesive sheet is deformed by external forces. Through research, the inventors have discovered that at a distance Ra of 15 or less, the compatibility of (meth)acrylic polymers (A) with isocyanate crosslinking agents (B) and their self-polymers increases.
[0036] The distance Ra can be below 14.5, below 14, below 13.5, below 13, below 12.5, and even below 12. The lower limit of the distance Ra is, for example, above 6.
[0037] The Hansen solubility parameter (HSP) is a parameter obtained by dividing the solubility parameter imported by Hildebrand into three components: dispersion term δD, polarity term δP, and hydrogen bonding term δH. δD represents the energy originating from intermolecular dispersion forces. δP represents the energy originating from intermolecular polarization forces. δH represents the energy originating from intermolecular hydrogen bonding forces. The unit for each component is typically MPa. 1 / 2 The above three components determine a point (vector) in a known three-dimensional space, which is Hansen's space. The distance Ra is the point (D) in the aforementioned space corresponding to the (meth)acrylic acid polymer (A). A P A H A ) and the point (D) corresponding to the self-polymer (C). C P C H C The distance between ) can be expressed by the formula: {4×(δD)} A -δD B ) 2 +(δP A -δP B ) 2 +(δH A -δH B ) 2} 1 / 2The detailed information on Hansen solubility parameters is available in "Hansen Solubility Parameters; A Users Handbook (CRC Press, 2007)". The δD, δP, and δH of the polymer can be determined by calculation, for example, using known software such as HSPiP (version 5), based on the structural units of the polymer and the content of those units in the polymer. More specifically, the δD, δP, and δH of each structural unit can be calculated separately, and the weighted average obtained by weighting the calculated δD, δP, and δH by the content of that unit is taken as the δD, δP, and δH of the polymer. The calculations are performed at a temperature of 23°C. It should be noted that the calculated values of δD, δP, and δH may sometimes differ slightly depending on the software used. However, this difference is usually negligible when calculating Ra. The calculation of the Hansen solubility parameters for crosslinking agents is only performed on those forming self-polymers.
[0038] In the calculation of distance Ra, the self-polymer (C) is envisioned as a single polymer formed from structural units derived from isocyanate crosslinking agents (B). However, it should be noted that the self-polymer of crosslinking agent (B) actually contained in the adhesive sheet formed by the adhesive composition (I) sometimes includes structural units other than those derived from the structural units of crosslinking agent (B).
[0039] The conditions for main heating satisfy the following equation (1) or (2). Where x and y are the heating temperature (°C) and time (seconds) in the main heating, respectively. Equation (2) means that when the heating temperature x exceeds 120°C, the heating time y should be limited to a given time. The heating temperature x can be determined as the highest temperature at which the coating film is exposed, for example, as the set temperature of a heating device such as a heating oven used for heating the coating film (in the case of multiple intervals with different set temperatures in the heating device, or when the set temperature changes over time, it is the highest set temperature at which the coating film is exposed in the heating device). The heating time y can be determined as the time the coating film is exposed at a temperature exceeding 120°C. When using a heating device, for example, the time y can be determined as the time the coating film is in a space with a set temperature exceeding 120°C, or the time the coating film passes through an interval with a set temperature exceeding 120°C. In the case of multiple intervals with set temperatures exceeding 120°C, the total time passed through that interval can be determined as the time y. When the set temperature changes over time, the time during which the set temperature exceeds 120°C can be calculated as time y. The same applies to the preheating temperature p and time q, which will be discussed later.
[0040] x≤120···(1)
[0041] x>120 and y≤-2.17x+365.83···(2)
[0042] According to the research of the inventors, isocyanate crosslinking agents (B) in monomeric state have poor solubility at high temperatures and tend to gradually aggregate inside the coated film. Therefore, the higher the temperature x and the longer the time y, the more likely the following tendency will be exhibited: the formation of the aforementioned independent domains in the adhesive sheet, and the size and density of the generated domains will increase. On the other hand, if the temperature x is below a certain level, the formation of oligomers such as dimers and trimers formed by the self-polymerization of crosslinking agents (B) will occur preferentially, and aggregation will be suppressed. Main heating under the conditions of satisfying the above formula (1) or (2) is suitable for suppressing the aggregation of crosslinking agents (B).
[0043] The lower limit of temperature x is, for example, above 80°C, above 85°C, and further above 90°C. The upper limit of temperature x is, for example, below 165°C, and below 160°C. Under the condition of satisfying equation (1), the upper limit of temperature x can be below 115°C, below 110°C, below 105°C, below 100°C, below 95°C, and further below 90°C. The temperature x of the main heating can remain constant during the main heating process, or it can change during the main heating period.
[0044] The lower limit of time y is, for example, more than 10 seconds, and can be more than 20 seconds, more than 30 seconds, more than 35 seconds, more than 40 seconds, more than 40 seconds, more than 45 seconds, and further more than 50 seconds. The upper limit of time y is, for example, less than 300 seconds, and can be less than 180 seconds, and further less than 180 seconds. Under the condition of satisfying equation (2), the upper limit of time y can be less than 100 seconds, less than 95 seconds, less than 90 seconds, less than 85 seconds, less than 80 seconds, less than 75 seconds, less than 70 seconds, less than 65 seconds, and further less than 60 seconds.
[0045] The main heating condition can satisfy the equation y ≤ -2.17x + 345.83 when x > 120. In the heating that satisfies the above equation, the time y is further restricted compared to the heating that satisfies equation (2).
[0046] The main heating condition can satisfy y≤80 when x>120, and further can satisfy y≤60.
[0047] The conditions for main heating can satisfy y<180 when x≤120, as well as y≤160, y≤140, y≤120, y≤110, y≤100, y<100, y≤95, and further satisfy y≤90.
[0048] The manufacturing method of this embodiment further includes preliminary heating of the coating film at a temperature p (°C) and a time q (seconds) before the main heating of the coating film of the adhesive composition (I). The preliminary heating temperature p is lower than the main heating temperature x. During preliminary heating, the main process is drying of the coating film; for solvent-based adhesive compositions (I), the main process is solvent removal. Solvent removal helps to suppress the aggregation of the isocyanate crosslinking agent (B). In addition, preliminary heating helps to suppress the melting of the isocyanate crosslinking agent (B) while allowing the reaction with a hydroxyl-containing compound, typically water, to proceed to a certain extent, thereby generating oligomers of the crosslinking agent (B).
[0049] The main heating temperature x (°C) and the preheating temperature p (°C) can satisfy the formula: xp ≤ 55. xp can be below 50°C, below 45°C, below 40°C, below 35°C, below 30°C, less than 30°C, below 25°C, below 20°C, below 15°C, and further below 10°C. The lower limit of xp exceeds 0°C, can be above 5°C, and further above 10°C. A small difference between temperature x and temperature p can help suppress the shrinkage of the coated film caused by rapid temperature changes.
[0050] The temperature p is, for example, above 50°C and below 80°C. The lower limit of temperature p can be above 55°C, above 60°C, above 65°C, and further above 70°C. The upper limit of temperature p can be below 75°C. The preheating temperature p can remain constant during the preheating process or it can change during the preheating period.
[0051] The time q can be 5 seconds or more, and can be 10 seconds or more, 15 seconds or more, 20 seconds or more, 25 seconds or more, 30 seconds or more, 35 seconds or more, 40 seconds or more, and can even be 45 seconds or more. The upper limit of the time q can be less than 180 seconds, and can be less than 120 seconds or less, 115 seconds or less, and can even be less than 110 seconds.
[0052] When the adhesive composition (I) is solvent-based, the time q can be set such that the solvent content in the coating film is 30% or less, preferably 25% or less, and more preferably 20% or less relative to the content before preheating.
[0053] The time q is represented by the ratio of the preheating time to the total preheating and main heating times, i.e., q / (q+y), which can satisfy 0.2≤q / (q+y)≤0.6. The lower limit of q / (q+y) can be above 0.25, and further above 0.3. The upper limit of q / (q+y) can be below 0.55, below 0.5, below 0.45, and further below 0.4.
[0054] Preheating can also be performed after a given time r has elapsed since the formation of the coated film. During the period from film formation to the start of preheating, time r is ensured to facilitate the effective removal of solvents contained in the coated film. Time r is, for example, 5–180 seconds, or 5–120 seconds, or 10–60 seconds. During time r, the coated film is in a non-heated atmosphere, for example, an atmosphere at 20–30°C.
[0055] Preheating and main heating can also be carried out continuously. As a more specific example, a heating device can be divided into a preheating zone and a main heating zone. With the temperatures x and p of each zone set independently, the coating film can be continuously transported from the preheating zone to the main heating zone.
[0056] The coated film supplied for the above-mentioned heating can be formed, for example, by coating an adhesive composition (I) or a mixture of adhesive composition (I) and a solvent onto a substrate film. The substrate film is typically a resin film or a metal film. The substrate film can also be a film obtained by performing a peeling treatment on the coated surface (a release film). In one example of a release film, the peeling treatment on the coated surface is performed using an organosilicon compound. Alternatively, the substrate film can also be an optical film, in which case an optical laminate comprising an adhesive sheet and an optical film can be formed.
[0057] The coating of the substrate film can be carried out using known methods. Coating can be carried out, for example, by roller coating, roller licking coating, gravure coating, reverse coating, roller brush coating, spraying, dip roller coating, bar coating, doctor blade coating, air knife coating, curtain coating, die lip coating, and extrusion coating using a die coating machine.
[0058] The compositions and mixtures coated on the substrate film preferably have a viscosity suitable for handling and application.
[0059] [Adhesive Composition (I)]
[0060] The adhesive composition (I) of this embodiment comprises a (meth)acrylic polymer (A) and a crosslinking agent (B). The (meth)acrylic polymer (A) is included in the adhesive composition (I) as a main component. In other words, the adhesive composition (I) is an acrylic adhesive composition. The main component refers to the component with the highest content in the composition. The content of the main component is, for example, 50% by weight or more, and can be 60% by weight or more, 70% by weight or more, 73% by weight or more, and more preferably 75% by weight or more.
[0061] ((Meth)acrylic polymer (A))
[0062] The (meth)acrylic polymer (A) preferably has structural units derived from a (meth)acrylic monomer (A1) having an alkyl group having 1 to 30 carbon atoms in its side chain as the main unit. The alkyl group can be linear or branched. The (meth)acrylic polymer (A) may have one or more structural units derived from the (meth)acrylic monomer (A1). Examples of (meth)acrylate monomers (A1) include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl ((meth)acrylate) lauryl (meth)acrylate, n-tridecyl (meth)acrylate, and n-tetradecyl (meth)acrylate. In this specification, "major unit" refers to a unit that, for example, occupies 50% or more by weight, preferably 60% or more by weight, more preferably 70% or more by weight, and even more preferably 80% or more by weight of all structural units possessed by the polymer.
[0063] (Meth)acrylic polymers (A) may have structural units derived from (meth)acrylic monomers (A1) having long-chain alkyl groups in their side chains. An example of such monomer (A1) is dodecyl (meth)acrylate (laurate). In this specification, "long-chain alkyl" refers to an alkyl group having 6 to 30 carbon atoms.
[0064] (Meth)acrylate polymers (A) can have structural units derived from (meth)acrylate monomers (A1) whose glass transition temperature (Tg) is in the range of -70 to -20°C when formed as homopolymers. An example of such monomer (A1) is n-butyl acrylate.
[0065] (Meth)acrylic polymers (A) may also have structural units other than those derived from (meth)acrylic monomers (A1). These structural units are derived from monomers (A2) capable of copolymerizing with (meth)acrylic monomers (A1). (Meth)acrylic polymers (A) may have one or more of these structural units.
[0066] Examples of monomers (A2) are aromatic ring monomers. Aromatic ring monomers can be aromatic ring (meth)acrylate monomers. Examples of aromatic ring monomers include phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, hydroxyethylated β-naphthol (meth)acrylate, and biphenyl (meth)acrylate. The content of structural units derived from aromatic ring monomers in the (meth)acrylate polymer (A) is, for example, 0–50% by weight, and can be 1–30% by weight, 5–25% by weight, 8–20% by weight, 10–18% by weight, 11–17% by weight, and further can be 12–16% by weight. The presence of structural units derived from aromatic ring monomers in the (meth)acrylate polymer (A) can contribute to improved compatibility between the (meth)acrylate polymer (A) and the crosslinking agent (B) and its self-polymers.
[0067] Other examples of monomers (A2) are hydroxyl-containing monomers. Hydroxyl-containing monomers can be hydroxyl-containing (meth)acrylate monomers. Examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylaurate (meth)acrylate, as well as methyl (4-hydroxymethylcyclohexyl)acrylate. It should be noted that hydroxyl groups can react with various crosslinking agents. From the viewpoint of improving the uniformity of the formed crosslinked structure, the content of structural units from hydroxyl-containing monomers in the (meth)acrylate polymer (A) can be less than 1% by weight, less than 0.5% by weight, further less than 0.1% by weight, or even 0% by weight (the structural unit may be absent).
[0068] The monomer (A2) can be a carboxyl-containing monomer, an amino-containing monomer, or an amide-containing monomer. Examples of carboxyl-containing monomers are (meth)acrylic acid, carboxyethyl (meth)acrylic acid, carboxypentyl (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, and butenoic acid. Examples of amino-containing monomers are N,N-dimethylaminoethyl (meth)acrylic acid and N,N-dimethylaminopropyl (meth)acrylic acid. Examples of amide-containing monomers include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxymethyl-N-propyl(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide, etc.; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl lactam monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam. By incorporating structural units from carboxyl-containing monomers, particularly acrylic acid, into (meth)acrylic polymers (A), the self-polymerization property of isocyanate crosslinking agents (B) can be improved, for example. This improved self-polymerization property of crosslinking agent (B) is particularly helpful in suppressing peeling of adhesive sheets in humid environments and in stabilizing the physical properties of adhesive sheets in systems with a high content of crosslinking agent (B).
[0069] The monomer (A2) can be a multifunctional monomer. Examples of multifunctional monomers include hexanediol di(meth)acrylate (1,6-hexanediol di(meth)acrylate), butanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl methacrylate, vinyl methacrylate, epoxy acrylate, polyester acrylate, and urethane acrylate, as well as divinylbenzene. The multifunctional acrylates are preferably 1,6-hexanediol diacrylate and dipentaerythritol hexa(meth)acrylate.
[0070] The total content of structural units derived from carboxyl-containing monomers, amino-containing monomers, amide-containing monomers, and polyfunctional monomers in the (meth)acrylic polymer (A) is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 8% by weight or less. When the (meth)acrylic polymer (A) contains this structural unit, the total content is, for example, 0.01% by weight or more, or possibly 0.05% by weight or more. The (meth)acrylic polymer (A) may also not contain structural units derived from polyfunctional monomers.
[0071] Examples of other monomers (A2) include alkoxyalkyl esters of methacrylates such as 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, methoxytriethylene glycol acrylate, 3-methoxypropyl acrylate, 3-ethoxypropyl acrylate, 4-methoxybutyl acrylate, and 4-ethoxybutyl acrylate; epoxy monomers such as glycidyl acrylate and methylglycidyl acrylate; sulfonic acid monomers such as sodium vinyl sulfonate; phosphate monomers; cyclopentyl acrylate, cyclohexyl acrylate, and isobornyl acrylate, which are methacrylates with alicyclic hydrocarbon groups; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins or dienes such as ethylene, propylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ethers; and vinyl chloride.
[0072] The total content of structural units from the other monomers (A2) mentioned above in the (meth)acrylic polymer (A) is, for example, 30% by weight or less, or 10% by weight or less, and preferably 0% by weight (excluding the structural unit).
[0073] (Meth)acrylic acid polymers (A) can be formed by polymerizing one or more of the aforementioned monomers using known methods. Polymerization can also be performed by polymerizing monomers with a portion of the monomer polymer. Polymerization can be carried out, for example, by solution polymerization, emulsion polymerization, bulk polymerization, thermal polymerization, or active energy radiation polymerization. Since adhesive sheets with excellent optical transparency can be formed, solution polymerization and active energy radiation polymerization are preferred. Polymerization is preferably carried out while avoiding contact between the monomers and / or a portion of the polymer and oxygen; for this purpose, polymerization can be performed, for example, in an inert gas atmosphere such as nitrogen, or in a state where oxygen is blocked using a resin film or the like. The (meth)acrylic acid polymer (A) to be formed can be any form of random copolymer, block copolymer, graft copolymer, etc.
[0074] The polymerization system that forms the (meth)acrylic acid polymer (A) may contain one or more polymerization initiators. The type of polymerization initiator can be selected according to the polymerization reaction, for example, it can be a thermal polymerization initiator or a photopolymerization initiator.
[0075] Solvents used in solution polymerization include, for example, esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and ketones such as methyl ethyl ketone and methyl isobutyl ketone, but the solvent is not limited to the above examples. The solvent can be a mixture of two or more solvents.
[0076] The polymerization initiators used in solution polymerization are, for example, azo polymerization initiators, peroxide polymerization initiators, and redox polymerization initiators. Examples of peroxide polymerization initiators include benzoyl peroxide and tert-butyl maleate peroxide. Among these, the azo polymerization initiator disclosed in Japanese Patent Application Publication No. 2002-69411 is preferred. Examples of such azo polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylbutyronitrile), dimethyl 2,2'-azobis(2-methylpropionic acid), and 4,4'-azobis(4-cyanopentanoic acid), but the polymerization initiator is not limited to the examples mentioned above. The amount of azo polymerization initiator used relative to 100 parts by weight of the total monomer is, for example, 0.05 to 0.5 parts by weight, or possibly 0.1 to 0.3 parts by weight.
[0077] The active energy rays used in active energy radiation polymerization include, for example, ionizing rays such as alpha rays, beta rays, gamma rays, neutron rays, and electron rays, as well as ultraviolet rays. Ultraviolet rays are preferred. Polymerization using ultraviolet irradiation is also called photopolymerization. The polymerization system of active energy radiation polymerization typically includes a photoinitiator. The polymerization conditions for active energy polymerization are not limited as long as a (meth)acrylic acid polymer (A) can be formed.
[0078] Photopolymerization initiators include, for example, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ol ketone photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzoyl photopolymerization initiators, ketal photopolymerization initiators, and thioxanone photopolymerization initiators, but photopolymerization initiators are not limited to the above examples.
[0079] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-olone-based photopolymerization initiators include 2-methyl-2-hydroxyphenylacetone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. Photoactive oxime photopolymerization initiators include, for example, 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl oxime). Benzoin photopolymerization initiators include, for example, benzoin. Benzoyl photopolymerization initiators include, for example, benzoyl. Benzophenone photopolymerization initiators include, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenyl ketone. Ketal photopolymerization initiators include, for example, benzoyldimethyl ketal. Thioxanone photopolymerization initiators include, for example, thioxanone, 2-chlorothioxanone, 2-methylthioxanone, 2,4-dimethylthioxanone, isopropylthioxanone, 2,4-diisopropylthioxanone, and dodecylthioxanone.
[0080] The amount of photopolymerization initiator used relative to the total amount of monomers (100 parts by weight) is, for example, 0.01 to 1 part by weight, or 0.05 to 0.5 parts by weight.
[0081] The weight-average molecular weight (Mw) of (meth)acrylic acid polymers (A) is, for example, 1 million to 2.8 million. From the viewpoint of durability and heat resistance of the adhesive sheet, it can be 1.2 million or more, and further, 1.4 million or more. The weight-average molecular weight (Mw) of polymers and oligomers in this specification is a value obtained based on GPC (gel permeation chromatography) determination (converted to polystyrene).
[0082] The content of (meth)acrylic polymer (A) in the adhesive composition (I), in terms of solids percentage, is, for example, 50% by weight or more, and may be 60% by weight or more, 70% by weight or more, and further may be 80% by weight or more. The upper limit of the content is, for example, 99% by weight or less, and may be 97% by weight or less, 95% by weight or less, 93% by weight or less, and further may be 90% by weight or less.
[0083] (Isocyanate crosslinking agent (B))
[0084] Isocyanate crosslinking agents (B) contain isocyanate groups as crosslinking reactive groups. Crosslinking agent (B) is typically a multifunctional crosslinking agent with two or more crosslinking reactive groups per molecule. Crosslinking agent (B) can also be a trifunctional or more crosslinking agent with three or more crosslinking reactive groups per molecule. The upper limit for the number of crosslinking reactive groups per molecule is, for example, five.
[0085] Isocyanate crosslinking agents (B) can be aromatic isocyanate compounds, alicyclic isocyanate compounds, or aliphatic isocyanate compounds.
[0086] Examples of aromatic isocyanate compounds that can be used as crosslinking agents (B) include phenyl diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and phenyl dimethyl diisocyanate.
[0087] Examples of alicyclic isocyanate compounds that can be used as crosslinking agents (B) include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated phenyl diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylphenyl diisocyanate.
[0088] Examples of aliphatic isocyanate compounds that can be used as crosslinking agents (B) include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylidene diisocyanate, 1,3-butylidene diisocyanate, dodecamethyl diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0089] The crosslinking agent (B) may also be a derivative of the above-mentioned isocyanate compound. Examples of derivatives include polymers (dimers, trimers, pentamers, etc.), adducts (adducts) obtained by addition reaction with polyols such as trimethylolpropane, urea-modified compounds, biuret-modified compounds, urethane-modified compounds, isocyanurate-modified compounds, carbodiimide-modified compounds, and urethane prepolymers obtained by addition reaction with polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, etc.
[0090] The crosslinking agent (B) is preferably an aromatic isocyanate compound or its derivatives, more preferably toluene diisocyanate or its derivatives (in other words, more preferably a toluene diisocyanate-based (TDI) crosslinking agent). TDI crosslinking agents exhibit superior reaction uniformity compared to phenyl diisocyanate or its derivatives (in other words, phenyl diisocyanate-based (XDI) crosslinking agents). Examples of TDI crosslinking agents include adducts of toluene diisocyanate with polyfunctional alcohols, and more specifically, trimethylolpropane / toluene diisocyanate trimer adducts.
[0091] The crosslinking agent (B) can be a commercially available product. Examples of commercially available products are Millionate MT, Millionate MTL, Millionate MR-200, Millionate MR-400, Coronate L, Coronate HL, and Coronate HX (all manufactured by Tosoh; all are trade names), and Takenate D-102, Takenate D-103, Takenate D-110N, Takenate D-120N, Takenate D-140N, Takenate D-160N, Takenate D-165N, Takenate D-170HN, Takenate D-178N, Takenate 500, and Takenate 600 (all manufactured by Mitsui Chemicals; all are trade names). The crosslinking agent (B) can preferably be Coronate L, Takenate D-102 and Takenate D-103 (all of which are trimethylolpropane / toluene diisocyanate trimer adducts).
[0092] The amount of crosslinking agent (B) in the adhesive composition (I) relative to 100 parts by weight of the (meth)acrylic polymer (A) is, for example, 1.5 parts by weight or more, 2 parts by weight or more, and more specifically, 2.5 parts by weight or more. The upper limit of the amount is, for example, 25 parts by weight or less, and can be 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, 10 parts by weight or less, 7 parts by weight or less, 5 parts by weight or less, and more specifically, 4 parts by weight or less.
[0093] The adhesive composition (I) may contain one or more crosslinking agents (B).
[0094] ((meth)acrylic acid oligomers)
[0095] The adhesive composition (I) may further comprise (meth)acrylic oligomers (D).
[0096] (Meth)acrylic acid oligomers (D) may have the same composition as the (meth)acrylic acid polymers (A) described above, except for the difference in weight-average molecular weight (Mw). The weight-average molecular weight (Mw) of (meth)acrylic acid oligomers (D) may be, for example, 1000 or more, or 2000 or more, 3000 or more, or even 4000 or more. The upper limit of the weight-average molecular weight (Mw) of (meth)acrylic acid oligomers may be, for example, 30000 or less, or 15000 or less, 10000 or less, or even 7000 or less.
[0097] (Meth)acrylate oligomers (D) include, for example, having one or more structural units derived from the following monomers: methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, heptyl methacrylate, octyl methacrylate, and propyl methacrylate. Isooctyl acrylate, nonyl acrylate, isononyl acrylate, decyl acrylate, isodecyl acrylate, undecyl acrylate, and dodecyl acrylate are alkyl methacrylates; esters formed from methacrylic acid and alicyclic alcohols, such as cyclohexyl acrylate, isobornyl acrylate, and dicyclopentyl acrylate; aromatic ring-containing methacrylates, such as phenyl acrylate and benzyl acrylate; and methacrylates obtained from terpene compound derivative alcohols.
[0098] Preferably, the (meth)acrylic oligomer (D) has structural units derived from (meth)acrylic monomers with relatively large bulk structures. In this case, the adhesiveness of the adhesive sheet can be further improved. Examples of such acrylic monomers are alkyl (meth)acrylic esters containing branched alkyl groups, such as isobutyl (meth)acrylate and tert-butyl (meth)acrylate; esters formed from (meth)acrylic acid and alicyclic alcohols, such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentyl (meth)acrylate; and aromatic (meth)acrylic esters containing aromatic rings, such as phenyl (meth)acrylate and benzyl (meth)acrylate. Preferably, the monomer has a cyclic structure, more preferably, it has two or more cyclic structures. In addition, from the viewpoint that ultraviolet irradiation is less likely to hinder polymerization and / or formation when the (meth)acrylic oligomer (D) is polymerized and / or the adhesive sheet is formed, the monomers are preferably not unsaturated bonds. For example, alkyl (meth)acrylic esters containing branched alkyl groups and esters formed from (meth)acrylic acid and alicyclic alcohols can be used.
[0099] Specific examples of (meth)acrylic oligomers (D) are copolymers of butyl acrylate, methyl acrylate and acrylic acid, copolymers of cyclohexyl methacrylate and isobutyl methacrylate, copolymers of cyclohexyl methacrylate and isobornyl methacrylate, copolymers of cyclohexyl methacrylate and acrylmorpholine, copolymers of cyclohexyl methacrylate and diethylacrylamide, copolymers of 1-adamantane acrylate and methyl methacrylate, copolymers of dicyclopentyl methacrylate and isobornyl methacrylate, homopolymers of dicyclopentyl acrylate, homopolymers of 1-adamantane methacrylate and 1-adamantane acrylate with methyl methacrylate, homopolymers of dicyclopentyl acrylate, homopolymers of 1-adamantane methacrylate and 1-adamantane acrylate.
[0100] The polymerization of (meth)acrylic oligomers (D) can be carried out using the polymerization method of (meth)acrylic polymers (A) described above.
[0101] When the adhesive composition (I) contains a (meth)acrylic oligomer (D), the amount of it incorporated relative to 100 parts by weight of the (meth)acrylic polymer (A) is, for example, 70 parts by weight or less, or even 50 parts by weight or less, and more preferably 40 parts by weight or less. The lower limit of the amount of it incorporated relative to 100 parts by weight of the (meth)acrylic polymer (A) is, for example, 1 part by weight or more, or even 2 parts by weight or more, and more preferably 3 parts by weight or more. The adhesive composition (I) may also not contain the (meth)acrylic oligomer (D).
[0102] (additive)
[0103] The adhesive composition (I) may also contain other additives. Examples of additives include crosslinking agents other than isocyanate crosslinking agents (B), silane coupling agents, colorants such as pigments and dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, rework improvers, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, antistatic agents (alkali metal salts, ionic liquids, ionic solids, etc., as ionic compounds), inorganic fillers, organic fillers, powders, particles, and foils such as metal powders. The additives may be formulated in a range of, for example, less than 10 parts by weight, preferably less than 5 parts by weight, and more preferably less than 1 part by weight, relative to 100 parts by weight of the (meth)acrylic polymer (A).
[0104] Examples of crosslinking agents other than isocyanate crosslinking agents (B) include peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, and multifunctional metal chelates. When the adhesive composition (I) contains a crosslinking agent other than isocyanate crosslinking agent (B), the total amount of the compounded agent relative to 100 parts by weight of the (meth)acrylic polymer (A) is preferably 0.1 to 5 parts by weight, more preferably in the order of 0.1 to 3 parts by weight, 0.1 to 2 parts by weight, and 0.1 to 1 part by weight. The adhesive composition (I) may also be free of crosslinking agents other than isocyanate crosslinking agent (B), such as epoxy crosslinking agents.
[0105] Examples of silane coupling agents include epoxy-containing silane coupling agents such as 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acryloylsilane coupling agents such as 3-acryloyloxypropyltrimethoxysilane and 3-methacryloyloxypropyltriethoxysilane; and isocyanate-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.
[0106] When the adhesive composition (I) contains a silane coupling agent, the amount of the agent relative to 100 parts by weight of the (meth)acrylic polymer (A) is, for example, 5 parts by weight or less, or 3 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.2 parts by weight or less, 0.1 parts by weight or less, and further, 0.05 parts by weight or less. The adhesive composition (I) may also be free of the silane coupling agent.
[0107] The adhesive composition (I) can be, for example, an emulsion type or a solvent type (solution type). From the viewpoint of being able to form an adhesive sheet with superior durability, the adhesive composition (I) can be solvent-based. Solvent-based adhesive compositions (I) may not contain UV curing agents or other light-curing agents.
[0108] [Adhesive sheet]
[0109] An example of an adhesive sheet obtained by the manufacturing method of this embodiment is shown below. Figure 1 . Figure 1 The adhesive sheet 1 is formed from an adhesive composition (I). The adhesive sheet 1 may, for example, contain a crosslinked polymer (A) of (meth)acrylic acid. The manufacturing method of this embodiment can produce an adhesive sheet having the following properties.
[0110] The thickness of the adhesive sheet 1 is, for example, 1 to 200 μm, and can be 5 to 150 μm, 10 to 100 μm, 10 to 75 μm, 10 to 50 μm, 10 to 40 μm, 10 to 30 μm, and further can be 10 to 20 μm.
[0111] The storage modulus G' (25°C) of the adhesive sheet 1 is, for example, 0.15 MPa or more, and can be 0.16 MPa or more, 0.17 MPa or more, or more specifically, 0.18 MPa or more. The upper limit of the storage modulus G' (25°C) is, for example, 5 MPa or less, and can be 3.0 MPa or less, 2.5 MPa or less, 2.0 MPa or less, 1.5 MPa or less, 1.0 MPa or less, 0.8 MPa or less, 0.6 MPa or less, 0.5 MPa or less, or more specifically, less than 0.5 MPa. Adhesive sheets 1 with a storage modulus G' within the above-mentioned range are particularly suitable for suppressing dimensional changes in the optical film.
[0112] The storage modulus (25°C) of the adhesive sheet 1 can be evaluated using the following method. First, a test sample is prepared from the material constituting the adhesive sheet 1. The test sample is disc-shaped, with a bottom diameter of 8 mm and a thickness of 2 mm. The test sample can be formed by punching a stack of multiple adhesive sheets 1 into a disc shape. Next, a dynamic viscoelasticity test is performed on the test sample. For example, an ARES-G2 tester manufactured by TA Instruments can be used for the dynamic viscoelasticity test. Based on the results of the dynamic viscoelasticity test, the storage modulus G' of the adhesive sheet 1 at 25°C can be determined. It should be noted that the conditions for the dynamic viscoelasticity test are as follows.
[0113] • Measurement conditions
[0114] Frequency: 1Hz
[0115] Deformation mode: Torsion
[0116] Measurement temperature: -70℃~150℃
[0117] Heating rate: 5℃ / min
[0118] The gel fraction of the adhesive sheet 1 is, for example, 60% or more, 65% or more, and more preferably 70% or more. The upper limit of the gel fraction is, for example, 99% or less, 98% or less, and more preferably 95% or less. The adhesive sheet 1 with a gel fraction within the above range is particularly suitable for suppressing dimensional changes in the optical film.
[0119] The gel fraction of adhesive sheet 1 can be evaluated using the following method. First, approximately 0.2 g of adhesive sheet 1 is scraped to obtain a small piece. Next, the obtained small piece is wrapped with a polytetrafluoroethylene (PTFE) stretched porous membrane (NTF1122, Nitto Denko, average pore size 0.2 μm) and tied with kite string to form a test piece. Next, the weight A of the obtained test piece is measured. Weight A is the total weight of the small piece of adhesive sheet, the stretched porous membrane, and the kite string. The total weight B of the stretched porous membrane and kite string used is measured beforehand. Next, the test piece is immersed in a 50 mL container filled with ethyl acetate and left to stand at 23°C for 1 week. After standing, the test piece is removed from the container and dried in a desiccator set to 130°C for 2 hours. The weight C of the test piece is then measured. The gel fraction of adhesive sheet 1 is calculated based on the measured weights A, B, and C, according to the formula: gel fraction (weight %) = (CB) / (AB) × 100 (%).
[0120] When the thickness is 75 μm, the haze of the adhesive sheet 1 is, for example, less than 1%, and can be less than 0.9%, less than 0.8%, less than 0.7%, less than 0.6%, less than 0.5%, less than 0.5%, less than 0.45%, less than 0.43%, less than 0.4%, and further less than 0.37%. The lower limit of haze is, for example, more than 0.1%, and can also be more than 0.2%. The above-mentioned haze values are obtained by the following method. It should be noted that the degree of whitening of the adhesive sheet 1 can be evaluated based on the above-mentioned haze. The haze of the adhesive sheet 1 can be measured according to Japanese Industry Standard (formerly known as Japanese Industrial Standard; JIS) K7136:1981.
[0121] When arbitrarily setting 10 evaluation regions of 1.5 μm square in the cross-sectional image of the adhesive sheet 1, and defining island-like regions with a minor axis of 100 nm or more as the first domain, the number of evaluation regions containing the first domain can be 5 or less, or 4 or less, 3 or less, 2 or less, 1 or less, or even 0. In this specification, a domain refers to an island-like region with a possible island structure that the adhesive sheet 1 may have. Furthermore, the minor axis of the domain can be determined as follows: the length of the shortest imaginary line segment imagined on the cross-sectional image, passing through the centroid of the domain and having the outer perimeter of the domain at both ends. It is preferable that the evaluation regions set on the cross-sectional image do not overlap. The cross-sectional image can be obtained, for example, by transmission electron microscopy (TEM). The magnification of the obtained cross-sectional image is, for example, 10,000 to 30,000 times. Regarding the domain, the adhesive sheet 1 in the above-described state is particularly suitable for suppressing dimensional changes in the optical film while ensuring transparency.
[0122] When arbitrarily defining 10 evaluation regions of 1.5 μm square in the cross-sectional image of the adhesive sheet 1, the shortest distance between adjacent first domains observed in these 10 evaluation regions can be 300 nm or more, 500 nm or more, or even 800 nm or more. A larger shortest distance indicates a lower density of the aforementioned domains in the adhesive sheet 1. It should be noted that the distance between adjacent domains can be defined as the distance between their outer perimeters.
[0123] When arbitrarily setting 10 evaluation regions of 1.5 μm square in the cross-sectional image of the adhesive sheet 1, and defining island-shaped regions with a minor axis of 50 nm or more and less than 100 nm as the second domain, the number of evaluation regions can be 3 or more, or 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, and even 10 or more, if the number of the second domain is less than that of the first domain. According to the research of the inventors, although the second domain is not as good as the first domain, it affects the durability and transparency of the adhesive sheet 1.
[0124] When arbitrarily setting 10 evaluation regions of 1.5 μm square in the cross-sectional image of the adhesive sheet 1, and defining island-shaped regions with a minor axis of 50 nm or more and less than 100 nm as the second domain, the shortest distance between adjacent second domains observed in the above 10 evaluation regions can be 150 nm or more, 175 nm or more, or even 200 nm or more.
[0125] When arbitrarily setting 10 evaluation regions of 1.5 μm square in the cross-sectional image of the adhesive sheet 1, and defining island-shaped regions with a minor axis of 50 nm or more and less than 100 nm as the second domain, the proportion (number ratio) of the second domains with the shortest distance between adjacent second domains of 100 nm or more among all the second domains observed in the above 10 evaluation regions can be 50% or more, 60% or more, or even 70% or more.
[0126] The state of the domain in adhesive sheet 1 can be evaluated, for example, by image analysis of the cross-sectional image. Image analysis can be performed using various software such as ImageJ.
[0127] The state of the domains in adhesive sheet 1 varies depending on the manufacturing conditions of adhesive sheet 1 (including the heating conditions described above). In addition, the state of the domains may also vary depending on the composition of the adhesive composition (I), the composition and properties (e.g., glass transition temperature) of the (meth)acrylic polymer (A), the type and amount of the crosslinking agent (B), and the type and amount of the additives.
[0128] The first and / or second domains may contain polymers of isocyanate crosslinking agents (B). Examples of polymers are self-polymers of crosslinking agent (B).
[0129] The adhesive sheet 1 can be used, for example, for optical applications. The adhesive sheet 1 can be used in optical laminates and / or image display devices. The adhesive sheet 1 is suitable for image display devices, such as those with narrow bezels or large screen sizes, where there is a particular requirement to suppress dimensional changes in the optical film. By being used in these image display devices, peeling of the film contained in the optical laminate can be suppressed, for example.
[0130] [Manufacturing method of optical laminates and optical laminates]
[0131] The method for manufacturing an optical laminate according to this embodiment is a method for manufacturing an optical laminate including an adhesive sheet and an optical film. The method includes forming an adhesive sheet using the aforementioned method for manufacturing the adhesive sheet. For example, the optical laminate can be manufactured by forming the adhesive sheet on a substrate film, which serves as the optical film, using the aforementioned method. Alternatively, it can be manufactured by forming the adhesive sheet on a transfer sheet, such as a release sheet, using the aforementioned method, and then transferring the formed adhesive sheet onto the optical film.
[0132] An example of an optical laminate obtained by the manufacturing method of this embodiment is shown below. Figure 2 . Figure 2 The optical laminate 10A includes an adhesive sheet 1 and an optical film 2, which are laminated together. The optical laminate 10A can be used in the form of an optical film with an adhesive sheet.
[0133] Examples of optical film 2 include a polarizer, a retardation film, and a laminated film comprising a polarizer and / or a retardation film. However, optical film 2 is not limited to the examples described above; it may also comprise a glass film.
[0134] The polarizer includes a polarizer. A protective film for the polarizer may be bonded to at least one side of the polarizer. Any adhesive or bonding agent may be used to bond the polarizer to the protective film. An adhesive sheet 1 may be used for bonding. The polarizer is typically a polyvinyl alcohol (PVA) film obtained by stretching in a gas atmosphere (dry stretching), stretching in boric acid water, or other methods to orient iodine.
[0135] A retardation film is a film that exhibits birefringence in the in-plane direction and / or the thickness direction. Examples of retardation films include stretched resin films and films obtained by aligning and immobilizing liquid crystal materials.
[0136] The retardation film can be a λ / 4 waveplate, a λ / 2 waveplate, a retardation film for antireflection (see, for example, paragraphs 0221, 0222, and 0228 of Japanese Patent Application Publication No. 2012-133303), a retardation film for viewing angle compensation (see, for example, paragraphs 0225 and 0226 of Japanese Patent Application Publication No. 2012-133303), or a tilted-orientation retardation film for viewing angle compensation (see, for example, paragraph 0227 of Japanese Patent Application Publication No. 2012-13303). The retardation film is not limited to the examples described above as long as it has birefringence in the in-plane direction and / or the thickness direction. There are no limitations on the phase difference value, arrangement angle, three-dimensional birefringence, or whether it is a single layer or multiple layers. Known films can be used as the retardation film.
[0137] The thickness of the optical film 2 is, for example, 1 to 200 μm. The thickness of the optical film 2, which serves as a polarizer, is, for example, 1 to 150 μm, and can be less than 100 μm, less than 75 μm, less than 50 μm, less than 20 μm, and more preferably less than 15 μm. The lower limit of the thickness can be more than 10 μm, more than 20 μm, more than 50 μm, more than 75 μm, and more preferably more than 100 μm.
[0138] The optical film 2 can be a single layer or a laminated film consisting of two or more layers. When the optical film 2 is a laminated film, the bonding of the layers can be achieved using an adhesive sheet 1.
[0139] Another example of an optical laminate obtained by the manufacturing method of this embodiment is shown below. Figure 3 . Figure 3 The optical laminate 10B has a laminated structure in which a release liner 3, an adhesive sheet 1, and an optical film 2 are sequentially stacked. The optical laminate 10B can be used in the form of an optical film with an adhesive sheet by peeling off the release liner 3.
[0140] The release liner 3 is typically a resin film. Examples of resins constituting the release liner 3 include polyesters such as polyethylene terephthalate (PET), polyolefins such as polyethylene and polypropylene, polycarbonate, acrylic acid, polystyrene, polyamide, and polyimide. The side of the release liner 3 that is in contact with the adhesive sheet 1 may also be subjected to a release treatment. The release treatment may be, for example, a treatment using an organosilicon compound. However, it should be noted that the release liner 3 is not limited to the above examples. The release liner 3 can be released when using the optical laminate 10B, for example, when it is adhered to the image forming layer.
[0141] Another example of an optical laminate obtained by the manufacturing method of this embodiment is shown below. Figure 4 . Figure 4The optical laminate 10C has a laminated structure in which a release liner 3, an adhesive sheet 1, a retardation film 2A, an interlayer adhesive 4, and a polarizer 2B are sequentially stacked. The optical laminate 10C can be used, for example, by pasting it onto an image forming layer after the release liner 3 has been peeled off.
[0142] The interlayer adhesive 4 can be a known adhesive, or the adhesive sheet 1 can be used for the interlayer adhesive 4.
[0143] Another example of an optical laminate obtained by the manufacturing method of this embodiment is shown below. Figure 5 , Figure 5 The optical laminate 10D has a laminated structure in which a release liner 3, an adhesive sheet 1, a retardation film 2A, an interlayer adhesive 4, a polarizer 2B, and a protective film 5 are sequentially stacked. The optical laminate 10D can be used, for example, by pasting the release liner 3 onto an image forming layer after the release liner 3 has been peeled off.
[0144] The protective film 5 functions to protect the outermost optical film 2 (polarizer 2B) during the circulation and storage of the optical laminate 10D, and also when the optical laminate 10D is introduced into the image display device. Furthermore, when introduced into the image display device, the protective film 5 can function as a window to the outside space. The protective film 5 is typically a resin film. The resin constituting the protective film 5 is, for example, polyester such as PET, polyolefins such as polyethylene and polypropylene, acrylic acid, cycloolefins, polyimide, and polyamide, preferably polyester. However, it should be noted that the protective film 5 is not limited to the above examples; it can also be a glass film or a laminate containing a glass film. Surface treatments such as anti-glare, anti-reflection, and antistatic treatments can be applied to the protective film 5.
[0145] The protective film 5 can be bonded to the optical film 2 by any adhesive, or it can be bonded using the adhesive sheet 1.
[0146] An optical laminate can have any configuration as long as it includes an adhesive sheet formed by the above-described method for manufacturing adhesive sheets.
[0147] The optical laminate obtained by the manufacturing method of this embodiment can be distributed and stored, for example, in the form of a wound body formed by winding a strip of optical laminate, or in the form of a single sheet of optical laminate.
[0148] The optical laminate obtained by the manufacturing method of this embodiment is typically used in image display devices. Image display devices include, for example, EL displays such as liquid crystal displays, organic EL displays, and inorganic EL displays.
[0149] [Manufacturing method of image display device and image display device]
[0150] The method for manufacturing an image display device according to this embodiment is a method for manufacturing an image display device having an optical laminate including an adhesive sheet and an optical film. The method includes forming an adhesive sheet by the adhesive sheet manufacturing method described above. The image display device can be manufactured, for example, using an adhesive sheet formed by the adhesive sheet manufacturing method described above, and / or an optical laminate formed by the optical laminate manufacturing method described above.
[0151] An example of an image display device obtained by the manufacturing method of this embodiment is shown below. Figure 6 . Figure 6 The image display device 11 has a stacked structure comprising a substrate 7, an image forming layer (e.g., an organic EL layer or a liquid crystal layer) 6, an adhesive sheet 1, a phase retardation film 2A, an interlayer adhesive 4, a polarizer 2B, and a protective film 5, which are sequentially stacked. Figures 2-5 The optical laminates 10A, 10B, 10C, and 10D (except for the release liner 3) are provided. The substrate 7 and the image forming layer 6 may have the same configuration as those of the substrate and image forming layer in a known image display device.
[0152] Figure 6 The image display device 11 can be an organic EL display or a liquid crystal display. However, the image display device 11 is not limited to this example; it can also be an electroluminescent (EL) display, a plasma display (PD), a field emission display (FED), etc. The image display device 11 can also be used in home appliances, automotive applications, public information displays (PIDs), etc.
[0153] An image display device may have any configuration as long as it includes an adhesive sheet formed by the above-described adhesive sheet manufacturing method and / or an optical laminate formed by the above-described optical laminate manufacturing method.
[0154] Example
[0155] The present invention will be described in more detail below through embodiments, but the present invention is not limited to the embodiments shown below.
[0156] First, the evaluation method for the (meth)acrylic polymers and adhesive sheets prepared in the examples and comparative examples is shown.
[0157] [Weight-average molecular weight (Mw)]
[0158] The weight-average molecular weight (Mw) of (meth)acrylic polymers was evaluated by GPC under the following conditions.
[0159] • Analytical apparatus: Waters, Acquity APC
[0160] • Chromatographic column: Tosoh G7000HXL+GMHXL+GMHXL
[0161] Column temperature: 40℃
[0162] • Eluent: Tetrahydrofuran (with added acid)
[0163] • Flow rate: 0.8 mL / min
[0164] Injection volume: 100μL
[0165] • Detector: Differential refractometer (RI)
[0166] • Standard sample: Agilent, polystyrene (PS)
[0167] [Distance Ra]
[0168] The distance Ra was calculated using the method described above. The software used was HSPiP (version 5).
[0169] [Storage modulus G'(25℃)]
[0170] The storage modulus G' (25°C) of the adhesive sheet was evaluated using the method described above. The laminate obtained by overlapping the fabricated adhesive sheets was punched into a disk shape to prepare the test sample. The dynamic viscoelasticity of the test sample was measured using a TA Instruments ARES-G2.
[0171] [Albinism]
[0172] Based on the haze measurement of the adhesive sheet, the degree of whitening of the adhesive sheet was evaluated as follows. The lower the haze, the lower the degree of whitening. The haze of the adhesive sheet was measured using a SUGA test mechanism haze meter HZ-V3 in an atmosphere at 25°C, based on JIS K7136:1981. The measurement was performed on the adhesive sheets of the evaluation object with 5 layers (15 μm thick adhesive sheet) or 3 layers (25 μm thick adhesive sheet) bonded on a Matsunami Glass Industry S012140 glass slide (1.3 mm thick) (total thickness 75 μm). For the adhesive sheet of Example 21 with a thickness of 35 μm, the measured value V of the state with 2 layers (total thickness 70 μm) was converted into a value equivalent to a total thickness of 75 μm by the formula: V×75 / 70.
[0173] A: The measured haze is less than 0.37%.
[0174] B: The measured haze is above 0.37% and below 0.43%.
[0175] C: The measured haze is above 0.43% and below 0.50%.
[0176] D: The measured haze is above 0.50%.
[0177] [Domain State]
[0178] The state of the adhesive sheet domains was evaluated using the aforementioned evaluation method based on cross-sectional images of the adhesive sheet. The cross-sectional images were obtained using a TEM (Hitachi, HT7820; accelerating voltage 100kV) with a magnification of 20,000x. The samples used for the TEM were prepared as follows: the adhesive sheet underwent heavy metal staining with RuO4, followed by resin embedding, and then approximately 100nm thick sections were cut using an ultrathin sectioning method. Ten evaluation regions were defined on the cross-sectional images in a non-overlapping manner. The state was evaluated by image analysis of the cross-sectional images using ImageJ. The states 1-5 of the evaluated domains and the evaluation criteria for each state are described below.
[0179] (State 1: There are evaluation regions in the first domain)
[0180] A: The number of evaluation areas is 0.
[0181] B: The number of evaluation areas is 1 to 2.
[0182] C: The number of evaluation areas is 3 to 5.
[0183] D: The number of evaluation areas is 6 or more.
[0184] (State 2: Shortest distance between adjacent first-order fields for all first-order fields)
[0185] A: The shortest distance is over 300nm.
[0186] D: Shortest distance less than 300nm
[0187] (State 3: Shortest distance between adjacent second fields for all second fields)
[0188] A: The shortest distance is over 200nm.
[0189] C: The shortest distance is more than 150nm and less than 200nm.
[0190] D: Shortest distance less than 150nm
[0191] (State 4: The number of evaluation regions in the second domain is less than 10)
[0192] A: The number of evaluation areas is 3 or more.
[0193] D: The number of evaluation areas is 1 to 2.
[0194] (State 5: The proportion of domains in all second domains where the shortest distance between adjacent second domains is greater than 100 nm)
[0195] A: More than 50%
[0196] D: Less than 50%
[0197] [Humidification Durability]
[0198] The humidification durability (equivalent to an accelerated durability test) of the adhesive sheets was evaluated using the following method. First, a circular polarizer with adhesive sheets was formed, having the adhesive sheets prepared in the examples and comparative examples on one exposed surface. Next, the circular polarizer was fixed to the surface of a glass plate (Corning, Eagle XG) via the aforementioned adhesive sheets. The fixing of the circular polarizer was carried out in an atmosphere of 23°C and 50% RH. Next, after treatment in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes, it was left to cool to 23°C to stabilize the bond between the circular polarizer and the glass plate. Then, it was placed in a heated and humidified atmosphere of 60°C and 95% RH for 500 hours. After placement, the atmosphere was returned to 23°C and 50% RH, and the humidification durability was evaluated by visually inspecting whether peeling of the circular polarizer from the glass plate had occurred and whether foaming had occurred between the glass plate and the circular polarizer, as described below.
[0199] A: No changes in appearance, such as foaming or peeling, were observed.
[0200] B: A small amount of isolated peeling or foaming was observed at the ends, but this is within the range that does not pose a problem in actual use.
[0201] C: A small amount of continuous peeling or foaming was observed at the end, but it was within the range that would not cause problems in actual use.
[0202] D: Obvious peeling or foaming was observed at the ends, indicating problems in actual use.
[0203] The following illustrates a method for forming a circular polarizer with an adhesive sheet used in the evaluation of humidification durability.
[0204] <Fabrication of Polarizer P1>
[0205] (Making a polarizing filter)
[0206] A long strip of polyvinyl alcohol (PVA) resin film (Kuraray, product name "PE3000", thickness 30 μm) was uniaxially stretched along its length (total stretching ratio 5.9 times) using a roller stretching machine. Simultaneously, the resin film underwent swelling, dyeing, crosslinking, cleaning, and drying processes to produce a 12 μm thick polarizer. In the swelling process, the resin film was stretched 2.2 times while being treated in pure water at 20°C. In the dyeing process, the resin film was stretched 1.4 times while being treated in an aqueous solution containing iodine and potassium iodide at a weight ratio of 1:7 at 30°C. The iodine concentration in the aqueous solution was adjusted to achieve a monomer transmittance of 45.0% for the produced polarizer. The crosslinking process employed two stages. In the first stage of crosslinking, the resin film was stretched 1.2 times while being treated in an aqueous solution containing dissolved boric acid and potassium iodide at 40°C. In the first stage of crosslinking treatment, the aqueous solution contained 5.0 wt% boric acid and 3.0 wt% potassium iodide. In the second stage of crosslinking treatment, the resin film was stretched 1.6 times while being treated in an aqueous solution containing dissolved boric acid and potassium iodide at 65°C. In the second stage of crosslinking treatment, the aqueous solution contained 4.3 wt% boric acid and 5.0 wt% potassium iodide. A potassium iodide aqueous solution at 20°C was used for the cleaning treatment. The aqueous solution used for the cleaning treatment contained 2.6 wt% potassium iodide. The drying treatment was carried out at 70°C for 5 minutes.
[0207] (Fabrication of polarizer P1)
[0208] Using a polyvinyl alcohol adhesive, a cellulose triacetate (TAC) film (manufactured by Konica Minolta, product name "KC2UA", thickness 25 μm) was bonded to each main surface of the polarizer fabricated above. A hard coating (7 μm thick) was formed on the main surface of the TAC film bonded to one of the main surfaces, opposite to the polarizer side. This resulted in a polarizer P1 with a protective layer with a hard coating / polarizer / protective layer (without hard coating).
[0209] <Fabrication of the phase difference film R1>
[0210] (Fabrication of the first phase retardation film)
[0211] 26.2 parts by weight of isosorbide (ISB), 100.5 parts by weight of 9,9-[4-(2-hydroxyethoxy)phenyl]fluorene (BHEPF), 10.7 parts by weight of 1,4-cyclohexanediethanol (1,4-CHDM), 105.1 parts by weight of diphenyl carbonate (DPC), and 0.591 parts by weight of cesium carbonate (0.2% aqueous solution) as a catalyst were added to a reaction vessel and dissolved under a nitrogen atmosphere (approximately 15 minutes). The temperature of the heat transfer medium in the reaction vessel was set to 150°C, and stirring was performed as needed. Next, the pressure inside the reaction vessel was reduced to 13.3 kPa, while the temperature of the heat transfer medium was raised to 190°C over 1 hour. The phenol produced as the temperature of the heat transfer medium increased was removed from the reaction vessel (the same procedure applies below). Next, the temperature inside the reaction vessel was maintained at 190°C for 15 minutes. Then, the pressure inside the reaction vessel was changed to 6.67 kPa, and the temperature of the heating medium was increased to 230°C over 15 minutes. At the moment the stirring torque of the agitator in the reaction vessel increased, the temperature of the heating medium was increased to 250°C over 8 minutes, and the pressure inside the reaction vessel was further reduced to below 0.200 kPa. After reaching the given stirring torque, the reaction was terminated, and the resulting reactants were extruded into water for granulation. This yielded a polycarbonate resin with a composition of BHEPF / ISB / 1,4-CHDM = 47.4 mol% / 37.1 mol% / 15.5 mol%. The obtained polycarbonate resin had a glass transition temperature of 136.6°C and a specific viscosity of 0.395 dL / g.
[0212] After vacuum drying the prepared polycarbonate resin granules at 80°C for 5 hours, a strip-shaped resin film with a thickness of 120 μm was obtained using a film-forming device equipped with a single-screw extruder (manufactured by Isuzu Chemical Industries, screw diameter 25 mm, cylinder set temperature 220°C), a T-die (width 200 mm, set temperature 220°C), a chilled roll (set temperature 120–130°C), and a winding machine. Next, the obtained resin film was stretched along its width using a tenter frame at a stretching temperature of 137–139°C and a stretch ratio of 2.5 times to obtain the first phase difference film.
[0213] (Fabrication of the second phase retardation film)
[0214] A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain type liquid crystal polymer (weight average molecular weight 5000) represented by the following chemical formula (I) (where 65 and 35 are molar percentages of each structural unit), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (BASF, trade name "Paliocolor LC242"), and 5 parts by weight of a photopolymerization initiator (Ciba Specialty Chemicals, trade name "IRGACURE 907") in 200 parts by weight of cyclopentanone. Next, the prepared liquid crystal coating solution was applied to the surface of a norbornene resin film (Zeon Chemicals, trade name "ZEONEX") serving as the substrate film using a wire-bar coater. The film was then heated at 80°C and dried for 4 minutes to orient the liquid crystal contained in the coating film. Finally, the coating film was cured by ultraviolet irradiation, forming a liquid crystal fixing layer (0.58 μm thick) on the substrate film as a second phase reversal film. The liquid crystal fixing layer has an in-plane phase difference Re of 0 nm for light with a wavelength of 550 nm, and a phase difference Rth of -71 nm in the thickness direction (nx = 1.5326, ny = 1.5326, nz = 1.6550). The liquid crystal fixing layer exhibits a refractive index characteristic of nz > nx = ny.
[0215] [Chemical Formula 1]
[0216]
[0217] (Fabrication of phase retardation film R1)
[0218] A phase retardation film R1 was fabricated by bonding one side of the first phase retardation film to the liquid crystal fixing layer of the second phase retardation film using an adhesive.
[0219] <Fabrication of a Circular Polarizing Film with Adhesive Sheets>
[0220] (Preparation of interlayer adhesive)
[0221] A monomer mixture containing 79.9 parts by weight of butyl acrylate, 15 parts by weight of benzyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet tube, and condenser. Next, 0.1 parts by weight of 2,2'-azoisobutyronitrile (2,2'-azoisobutyronitrile), as a polymerization initiator, was added along with ethyl acetate to 100 parts by weight of the monomer mixture. After nitrogen purging of the flask by slowly stirring and introducing nitrogen, the liquid temperature in the flask was maintained at approximately 55°C, and the polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction solution to adjust the solids concentration to 30% by weight, yielding a solution of a (meth)acrylic acid polymer for use as an interlayer adhesive. The weight-average molecular weight of the obtained polymer was 2.2 million.
[0222] Next, in the obtained solution of (meth)acrylic acid polymer, 0.5 parts by weight of trimethylolpropane / toluene diisocyanate trimer adduct (Tosoh, trade name "CoronateL"), 0.1 parts by weight of benzoyl peroxide as a peroxide crosslinking agent, 0.2 parts by weight of epoxy-containing silane coupling agent (Shin-Etsu Chemical Industry, trade name "KBM-403") and 0.5 parts by weight of a polyether compound with reactive silyl groups (Kaneka, Silyl SAT10) were mixed, relative to 100 parts by weight of the solid component of the solution, to obtain the adhesive composition PSA1 used in the interlayer adhesive for bonding polarizer P1 to phase retardation film R1.
[0223] (Fabrication of a polarizer with an interlayer adhesive layer)
[0224] The adhesive composition PSA1 prepared above was coated onto the release surface of a 38 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical Polyester Film, MRF38) to achieve a dried layer thickness of 12 μm, and dried at 155°C for 1 minute to form an interlayer adhesive layer. The polyethylene terephthalate (PET) film is a release film whose release surface has been treated with silicone. Next, the formed interlayer adhesive layer was transferred to the protective layer (without hard coating) side of the polarizer P1 to obtain a polarizer with an interlayer adhesive layer.
[0225] (Fabrication of a circular polarizer with adhesive pads)
[0226] Each adhesive sheet prepared in the examples and comparative examples was transferred from the release film to the second retardation film side of the retardation film R1 (the norbornene resin film used as the substrate film during the preparation of the second retardation film was peeled off) and attached. Next, the polarizer prepared above with the interlayer adhesive layer was attached to the first retardation film side of the retardation film R1 via the interlayer adhesive layer, resulting in a circular polarizer with adhesive sheets. The attachment of the retardation film R1 to the polarizer with the interlayer adhesive layer was performed such that the angle between the slow axis of the first retardation film and the absorption axis of the polarizer was 45 degrees counterclockwise when viewed from the first retardation film side.
[0227] [Condensation marks (appearance)]
[0228] We visually confirmed whether droplet marks were generated on the surface of the release film and coating film (adhesive sheet) after the main heating, and evaluated the condensation marks that may occur during the manufacturing of the adhesive sheet as described below.
[0229] A: No trace of droplets was observed.
[0230] B: A small amount of droplet traces were observed, but the level is sufficient for practical use without any problems.
[0231] C: Traces of droplets were observed, indicating a problem in actual use.
[0232] [Degree of residue]
[0233] To determine the content of residual monomers and solvents in the adhesive sheet formed on the release liner, the extent of residues was evaluated as described below. It should be noted that ppm is by weight.
[0234] A: The content of residual monomers and residual solvents are both below the detection limit.
[0235] B: The combined content of residual monomers and residual solvents is above the detection limit and below 50 ppm.
[0236] C: The combined content of residual monomers and residual solvents exceeds 50 ppm but is less than 100 ppm.
[0237] D: The combined content of residual monomers and residual solvents exceeds 100 ppm.
[0238] (Method for determining residual monomers)
[0239] Approximately 0.1 g of adhesive sheet was collected from a threaded tube, and 5 mL of acetone was added. The mixture was shaken overnight. The contents of the threaded tube were then filtered through a membrane filter (average pore size 0.45 μm), and 1 μL of the resulting filtrate was injected into a gas chromatograph (GC) to determine the content of residual monomers. The GC determination conditions are shown below.
[0240] GC device: Agilent Technologies, 6890N
[0241] Column: Agilent Technologies HP-1 (0.250mm φ × 30m, df = 1.0μm)
[0242] Column temperature: After holding at 40°C for 1 minute, increase the temperature to 60°C (at a rate of 5°C / min), then increase it to 140°C (at a rate of 10°C / min), and then increase it to 300°C (at a rate of 20°C / min), holding at 300°C for 10 minutes.
[0243] Column flow rate: 2 mL / min (He)
[0244] Column pressure: Constant flow mode (136 kPa)
[0245] Inlet temperature: 200℃
[0246] Injection volume: 1μL
[0247] Injection method: Stream splitting (10:1)
[0248] Detector: Flame Ionization Detector (FID)
[0249] Detector temperature: 250℃
[0250] (Method for determining residual solvent)
[0251] Approximately 0.02 g of adhesive film was collected and sealed into a 20 mL headspace sample vial. Next, the vial containing the adhesive film was heated in a headspace sampler (HSS) at 150 °C for 30 minutes. One mL of the gas phase remaining in the vial after heating was injected into the GC, and the residual solvent content was determined. The HSS and GC determination conditions are shown below.
[0252] HSS conditions
[0253] HSS device: Agilent Technologies, G1888
[0254] Heating temperature: 150℃
[0255] Heating time: 30 minutes
[0256] Pressurization time: 0.20 minutes
[0257] Cycle filling time: 0.20 minutes
[0258] Cycle balancing time: 0.05 minutes
[0259] Injection time: 0.50 minutes
[0260] Sample cycling temperature: 160℃
[0261] Transmission line temperature: 200℃
[0262] • GC determination conditions (residual solvent)
[0263] GC device: Agilent Technologies, 6890N
[0264] Column: Agilent Technologies HP-1 (0.250mm φ × 30m, df = 1.0μm)
[0265] Column temperature: Hold at 40°C for 3 minutes, then increase to 120°C (rate 10°C / min), then increase to 300°C (rate 20°C / min), and hold at 300°C for 10 minutes.
[0266] Column flow rate: 1 mL / min (He)
[0267] Column pressure: Constant flow mode (81 kPa)
[0268] Inlet temperature: 250℃
[0269] Injection volume: 1 mL
[0270] Injection method: Split (20:1)
[0271] Detector: FID
[0272] Detector temperature: 250℃
[0273] [Overall Evaluation]
[0274] A comprehensive evaluation of the durability and transparency of the adhesive sheet was conducted as described below.
[0275] A: The humidification durability is rated A, and the whitening is rated A to C.
[0276] B: The humidification durability is rated as B, and the whitening is rated as A to C.
[0277] C: The humidification durability is rated as C, and the whitening is rated as A to C.
[0278] D: The evaluation of at least one of humidification durability and whitening is D.
[0279] Next, the methods for manufacturing each adhesive sheet of the embodiments and comparative examples will be described.
[0280] The abbreviations or names shown in the following description correspond to the compounds as follows.
[0281] BA: n-Butyl acrylate
[0282] BzA: Benzyl acrylate
[0283] AA: Acrylic acid
[0284] HBA: 4-Hydroxybutyl acrylate
[0285] AIBN: 2,2'-Azobisisobutyronitrile
[0286] C / L: Trimethylolpropane / Toluene diisocyanate trimer adduct (isocyanate crosslinking agent; Tosoh Corporation, Coronate L)
[0287] TetradC: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (multifunctional epoxy crosslinking agent; manufactured by Mitsubishi Gas Chemical, Tetrad C)
[0288] KBM403: 3-Epoxypropoxypropyltriethoxysilane (Silane coupling agent; manufactured by Shin-Etsu Chemical Industry, KBM403)
[0289] [Preparation of (meth)acrylic polymer (A)]
[0290] (Synthesis example 1)
[0291] In a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet tube, and condenser, 94.9 parts by weight of BA, 5.0 parts by weight of AA, and 0.1 parts by weight of HBA were added. Next, 0.1 parts by weight of AIBN as a polymerization initiator was added to 100 parts by weight of the BA, AA, and HBA mixture. After nitrogen purging of the flask by slowly stirring and introducing nitrogen, the liquid temperature in the flask was maintained at approximately 55°C, and the polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction solution to adjust the solids concentration to 12% by weight, yielding a solution of (meth)acrylic acid polymer (A-1). The weight-average molecular weight (Mw) of (meth)acrylic acid polymer (A-1) was 2.2 million. Regarding HSP, the δD, δP, and δH of (meth)acrylic acid polymer (A-1) were 16.75 MPa. 1 / 2 3.49MPa 1 / 2 and 5.38MPa 1 / 2 .
[0292] (Synthesis example 2)
[0293] The monomers used were changed to 79.9 parts by weight of BA, 15.0 parts by weight of BzA, 5.0 parts by weight of AA, and 0.1 parts by weight of HBA. Otherwise, a solution of (meth)acrylic acid polymer (A-2) was obtained in the same manner as in Synthesis Example 1. The weight-average molecular weight (Mw) of (meth)acrylic acid polymer (A-2) was 2.2 million. Regarding HSP, the δD, δP, and δH of (meth)acrylic acid polymer (A-2) were 17.05 MPa. 1 / 2 3.49MPa 1 / 2 and 5.43MPa 1 / 2 .
[0294] (Synthesis example 3)
[0295] The monomers used were changed to 74.9 parts by weight of BA, 20.0 parts by weight of BzA, 5.0 parts by weight of AA, and 0.1 parts by weight of HBA. Otherwise, a solution of (meth)acrylic acid polymer (A-3) was obtained in the same manner as in Synthesis Example 1. The weight-average molecular weight (Mw) of the (meth)acrylic acid polymer (A-3) was 2.3 million. Regarding HSP, the δD, δP, and δH of the (meth)acrylic acid polymer (A-3) were 17.15 MPa. 1 / 2 3.49MPa 1 / 2 and 5.44MPa1 / 2 .
[0296] The types and amounts of monomers and polymerization initiators used in Synthetic Examples 1-3, and the resulting polymers, are summarized in Table 1 below for their weight-average molecular weight (Mw) and HSP distance Ra. It should be noted that the δD, δP, and δH of the C / L self-polymers are 20.50 MPa. 1 / 2 12.40MPa 1 / 2 and 9.60MPa 1 / 2 .
[0297] [Table 1]
[0298]
[0299] [Preparation of adhesive compositions and adhesive sheets]
[0300] (Manufacturing Examples 1-8)
[0301] As shown in Table 2 below, a solvent-based adhesive composition was obtained by mixing a crosslinking agent and the like with 100 parts by weight of the solid component of (meth)acrylic polymer (A).
[0302] [Table 2]
[0303]
[0304] ※The unit of measurement for the amount of ingredients is parts by weight.
[0305] Next, the release surface of a 38 μm thick PET film (Mitsubishi Chemical Polyester Film, MRF38) with an organosilicon-treated release film was coated with the adhesive composition prepared in each manufacturing example to form a coated film. This coated film was placed in an environment of 23°C until preheating (placement time r). Then, while transporting the substrate film and the coated film, continuous preheating and main heating were performed in an air-circulating constant-temperature oven to form adhesive sheets of Examples 1-25 and Comparative Examples 1-5 with given thicknesses. The placement time r and the conditions for preheating and main heating are shown in Table 3 below. It should be noted that the preheating and main heating temperatures are the set temperatures of the preheating zone and the main heating zone in the oven, respectively. The preheating and main heating times are the times the substrate film and the coated film pass through the preheating zone and the main heating zone, respectively.
[0306] [Table 3]
[0307]
[0308] The evaluation results of the fabricated adhesive sheet are shown in Table 4 below. Additionally, regarding the fabricated adhesive sheet, the main heating temperature and time, as well as the overall evaluation results, are presented in... Figure 7It should be noted that the states 1 to 5 of the domains in Table 4 are described below.
[0309] State 1: There are evaluation regions in the first domain.
[0310] State 2: Shortest distance between adjacent first-order fields for all first-order fields.
[0311] State 3: Shortest distance between adjacent second domains for all second domains.
[0312] State 4: The number of evaluation regions in the second domain is less than 10.
[0313] State 5: The proportion of all second-domain regions where the shortest distance between adjacent second-domain regions is greater than 100 nm.
[0314] [Table 4]
[0315]
[0316] As shown in Table 4, compared with the adhesive sheet of the comparative example, the adhesive sheet of the embodiment is suitable for suppressing dimensional changes and has excellent transparency and durability.
[0317] Industrial applicability
[0318] According to the manufacturing method of the present invention, an optical adhesive sheet for use in, for example, optical laminates and / or image display devices can be formed.
Claims
1. A method for manufacturing an adhesive sheet, the method comprising: A coating film containing an adhesive composition comprising a (meth)acrylic polymer (A) as a main component and further comprising an isocyanate crosslinking agent (B) is preheated under heating conditions of temperature p (°C) and time q (seconds). After the preheating, the coated film is heated under the conditions of temperature x (°C) and time y (seconds) to form an adhesive sheet. The (meth)acrylic polymer (A) comprises structural units derived from aromatic ring monomers, and the content of the structural units derived from aromatic ring monomers in the (meth)acrylic polymer (A) is 1-30% by weight. When considering the self-polymer (C) of the isocyanate crosslinking agent (B), the distance Ra of the Hansen solubility parameter (HSP) between the (meth)acrylic acid polymer (A) and the self-polymer (C) is less than 15. The preheating temperature p is lower than the heating temperature x, and is above 50°C but less than 80°C. The heating temperature x and the preheating temperature p satisfy the equation: xp≤55. The heating temperature x and the heating time y satisfy the following equation (1) or (2). x≤120 ···(1) x>120 and y≤-2.17x+365.83 ···(2).
2. The method for manufacturing the adhesive sheet according to claim 1, wherein, The heating condition satisfies y < 180 when x ≤ 120.
3. The method for manufacturing the adhesive sheet according to claim 1, wherein, The heating condition satisfies y < 100 when x ≤ 120.
4. The method for manufacturing the adhesive sheet according to claim 1, wherein, The heating temperature x is above 80°C.
5. The method for manufacturing the adhesive sheet according to claim 1, wherein, The preheating time q is 40 seconds or more.
6. The method for manufacturing the adhesive sheet according to claim 1, wherein, When the preheating time q is expressed as the ratio of the preheating time q to the total of the preheating time q and the heating time y, i.e., q / (q+y), the condition 0.2≤q / (q+y)≤0.6 is met.
7. The method for manufacturing the adhesive sheet according to claim 1, wherein, The adhesive sheet is formed having a storage modulus G' of 0.15 MPa or higher at 25°C.
8. The method for manufacturing the adhesive sheet according to claim 1, wherein, The adhesive sheet is formed having a haze of less than 1%.
9. The method for manufacturing the adhesive sheet according to claim 1, wherein, The amount of the isocyanate crosslinking agent (B) in the adhesive composition is 1.5 parts by weight or more relative to 100 parts by weight of the (meth)acrylic polymer (A).
10. The method for manufacturing the adhesive sheet according to claim 1, wherein, The isocyanate crosslinking agent (B) is toluene diisocyanate.
11. The method for manufacturing the adhesive sheet according to claim 1, wherein, The (meth)acrylic polymer (A) contains structural units derived from hydroxyl-containing monomers at a content of less than 1% by weight.
12. The method for manufacturing the adhesive sheet according to claim 1, wherein, The adhesive composition is a solvent-based adhesive composition.
13. A method for manufacturing an optical laminate, the optical laminate comprising an adhesive sheet and an optical film, the method comprising: The adhesive sheet is formed by the method for manufacturing the adhesive sheet according to any one of claims 1 to 12.
14. A method for manufacturing an image display device, the image display device comprising an optical laminate including an adhesive sheet and an optical film, the method comprising: The adhesive sheet is formed by the method for manufacturing the adhesive sheet according to any one of claims 1 to 12.
Citation Information
Patent Citations
Acrylic adhesives and its production method
JP2002069411A
Adhesive, polarizing plate with adhesive and manufacturing method thereof
JP2008031214A
Polarizing plate and liquid crystal display device
JP2009098665A
Draining device, and indoor unit of air conditioner
JP2012013303A
Optical display device having polarizing film
JP2012133303A
